Public Relations Goal—Telling How Agricultural Progress Benefits All - O. B. Copeland (Journal of Applied Communications, 1970)
It may be trite to list the production marvels in agriculture for the various "publics" with whom we work through universities, agri-business firms, government agencies, and the like.